2002
DOI: 10.1002/ldr.525
|View full text |Cite
|
Sign up to set email alerts
|

Microtopography as a factor in the degradation of Vertisols in central India

Abstract: Earlier studies on soil degradation in Vertisols of the Purna Valley of central India indicated that the semiarid climate characterized by a mean annual rainfall (MAR) of 875 mm and a tropustic moisture regime is responsible for the development of calcareous sodic soils. Recent observations, however, indicate that in the adjacent east upland of the Purna Valley, namely in the Pedhi Watershed, Vertisols have drainage problems, although the area receives a higher MAR than the Purna Valley, the total MAR being 97… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…This relation with the landscape position has also been reported by other studies. Geostatistics may help evaluation of spatial dependence of chemical attributes in the landscape, with the nutrient availability at least partially controlled by the position of the landscape (Amador et al, 1997 andVaidya &Pal, 2002). Furthermore, Brubaker et al (1993) and Vaidya & Pal (2002) reported that soil chemical attributes and position in the landscape are interrelated, as also reported in the present study.…”
Section: Resultssupporting
confidence: 81%
“…This relation with the landscape position has also been reported by other studies. Geostatistics may help evaluation of spatial dependence of chemical attributes in the landscape, with the nutrient availability at least partially controlled by the position of the landscape (Amador et al, 1997 andVaidya &Pal, 2002). Furthermore, Brubaker et al (1993) and Vaidya & Pal (2002) reported that soil chemical attributes and position in the landscape are interrelated, as also reported in the present study.…”
Section: Resultssupporting
confidence: 81%
“…In contrast, in swell-shrink soils of central India a reverse situation was observed; sodic soils occur in MH and non-sodic soils as ML position. Relatively higher amounts of PC and subsoil sodicity in MH Vertisols than in ML soils suggest the formation MH sodic soils which is due to relatively more aridity on MH than the ML positions 19 . Thus the development of CaCO 3 and sodicity in the soils of ML and MH positions may be widespread in similar SAT areas of India.…”
Section: Micro Topography: As Factor Of Natural Soil Degradation In Satmentioning
confidence: 96%
“…Although selected pedogenic processes such as laterization, hard setting, fragipan formation and claypan formation are hitherto considered as natural soil degradation processes as they lead to less desirable physical and chemical conditions, causing degradation of soils 7,8 , the majority of the information on soil degradation at national 9,10 , regional 11 or international level 12,13 has focused only on anthropogenic degradation. However, a few recent reports on major soil types (Indo-Gangetic Plains or IGP, red ferruginous and deep black soils) at the National Bureau of Soil Survey and Land Use Planning (NBSS&LUP, ICAR), Nagpur, India showed that the development of sodicity and accumulation of relatively higher amounts of exchangeable Mg (EMP) than that of exchangeable Ca (ECP) in soils are also a natural process of soil degradation in the SAT climatic conditions 1,3,[14][15][16][17][18][19][20] .…”
Section: Definition Processes and Factors Of Soil Degradationmentioning
confidence: 99%
See 2 more Smart Citations